Suistanable Development Goals Protect Extinction of biodiversity Nepenthes sp: Array - Mingle A Pistanty (Yayasan Citra Dharma Cindekia, 2022)
Nepenthes populations in nature are thought to be decreasing due to several factors such as forest fires, conversion of forest land or shrubs to residential areas, cultivation, plantations, agriculture or mining. The government has determined that Nepenthes is one of the priority plant species for protection because its presence in nature tends to be endangered. The existence of Nepenthes in their natural habitat has begun to be threatened due to several factors, including conversion into agricultural and mining lands, damage to natural habitats due to disasters or human actions, as well as over-exploitation. Based on these facts, Nepenthes plants are included in protected plants based on IUCN, WCMC, and Government Regulation N0. 7 of 1999 concerning Preservation of Plants and Animals. A study on the extinction of Nepenthes was carried out to find out the factors that influenced the extinction of this plant. The method used in this research is library search. Some previous research is used as a reference in this discussion in depth. The results show that there are several causes of the extinction of biodiversity for the pitcher plant, including habitat degradation, habitat fragmentation, exploitation, invasive species, and climate change. Real world programs and actions in the SGD's (Suistanable Development Goals) as an effort to protect the pitcher plant (Nepenthes sp.) from the threat of extinction of biodiversity is to carry out conservation efforts both in situ and ex situ.